PENGARUH DANCE MOVEMENT THERAPY DAN TARI KELINCIKU TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 4-5 TAHUN - Fadillah, Nailatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Background: Motor development of preschool age children plays an important role in the health and development of children, and is the basis for good physical activity. This study aims to determine the effect of dance movement therapy intervention and rabbit dance intervention on gross motor development of children aged 4-5 years. Methods: The design used in this study is a quasi experiment with a sample of 34 respondents with purposive sampling technique. This study uses the Denver Developmental Screening Test (DDST) sheet. Result: The results of the univariate test showed that most of the respondents were 5 years old with a percentage of 25 people (73.5%), and the majority of respondents were male with a percentage of 22 people (64.7%).alternative Wilcoxon can be seen that the p value (0.025) < (0.05) in group 1 of the Dance Movement Therapy has an effect on the motor development of children aged 4-5 years. In group 2 with p value (0.002) < (0.05) the rabbit dance intervention affected the gross motor development of children aged 4-5 years. Alternative test results Mann Whitney (0.089) > (0.05) means that there is no significant difference between posttest group 1 and posttest group 2. Conclucion: based on observation result rabbit dance intervention are more effective than using Dance Movement Therapy intervention. The results of this study are expected to improve gross motor development of children aged 4-5 years.